Aula de campo em uma escola situada em Maranguape-CE: um estudo de caso com alunos do ensino médio - Abreu, Leiza Jane Lopes Lima (2019)
The teaching of biology involves many concepts, which must be passed on by teachers so that the student learns, not only memorizes. However, one of the major challenges faced by teachers is actually learning their students. One strategy that may be significant is the field lessons, since the student has the possibility to recognize in practice the theoretical knowledge acquired in the classroom. Thus, the field class, if well planned, can be used by the teacher as a teaching tool. In this perspective, this dissertation has the general objective to investigate the field classes as a tool in the Teaching of Biology of the Secondary School of the Center for Comprehensive Attention to Children (CAIC), Senator Carlos Jereissati, located in the city of Maranguape-Ceará. The subjects are 35 students from two classes, one from the 2nd and the other from the 3rd year, and the teacher from the subject of Biology. The initial methodology was the exposition of the contents through the theoretical classes on the mangrove biome, followed by the field lesson at the Eco Museum Mangue Natural (EcoMuNaM), located in the city of Fortaleza-Ceará. The research was characterized as a case study with a qualitative and quantitative approach. As a research tool, in addition to the direct observations and field diary records, a semi-structured questionnaire was applied to the students after the lectures, and a structured interview after the field lesson. For the teacher, a semi-structured questionnaire was applied to diagnose the main challenges and difficulties encountered in the planning and execution of a field lesson, as well as evaluation of the effectiveness of the field class as a teaching tool. As an educational product will be presented a Guide to planning field lessons, with the purpose of guiding and contributing to the planning and carrying out of these activities.